How Well Has the Romanian Higher Education Prepared Graduates for the Labor Market Changes in the Last Decade? A PRISMA-Guided Systematic Review of Outcomes and Demand Trends - Vuc, Daria Elisa; Stroe, Viorela-Denisa (Theoretical and Practical Research in Economic Fields; Vol 17 No 1 (2026): TPREF Volume XVII Issue 1(37) March 2026, 2026)
Persistent skills mismatches and overqualification among Romanian graduates highlight a gap between higher education outcomes and labor market needs. Technological transitions have amplified the demand for transversal, digital, and green competences, yet Romanian universities remain largely theoretical and slow to adapt. Objective: This systematic review aimed to synthetize evidence on the evolution of employability skills in Romania (2015-2025) and assess the alignment between higher education and labor market requirements. Eligibility criteria: Peer-reviewed empirical and theoretical studies from 2015 to 2025, addressing employability, skills mismatch, higher education, and digital competencies in Romania were included. Information sources: Data were retrieved from Scopus, Web of Science, and relevant EU institutional repositories. Methods: Following PRISMA 2020 guidelines, 36 studies were selected through a multi-stage screening (identification, eligibility, inclusion). Quantitative, qualitative, and mixed-method studies were synthetized thematically. Results: The findings show persistent skill mismatches, limited internship opportunities, and weak university – industry collaboration. Limitations: The review excludes non-English and grey literature and relies on cross-sectional data, limiting generalization and longitudinal insight. Conclusions: Romania’s higher education system shows gradual progress toward skill alignment, but needs structural reform to meet technological, digital, and sustainability challenges.